2019
DOI: 10.32800/abc.2019.42.0317
|View full text |Cite
|
Sign up to set email alerts
|

Towards inclusion of genetic diversity measures into IUCN assessments: a case study on birds

Abstract: The IUCN Red List categorizes species based on their geographical distribution and population size. However, attributes such as genetic information are not yet considered. We compiled information on genetic diversity (HE, HO) and inbreeding coefficient (f) along with their ecological attributes (IUCN category, migratory habit, forest dependence and habitat type) from a literature survey to assess whether bird species categorized as being of highest conservation concern display the lowest genetic diversity. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 108 publications
2
12
0
Order By: Relevance
“…This study highlights the importance of using genetic data in the risk analysis of a species, as suggested by Garner et al [8], Victorino et al [16], and Lanes et al [17]. The genetic results and simulations included in the MER [26] suggest that the species is in danger of extinction and not threatened, as reported by Clark-Tapia et al [21] using only ecological data.…”
Section: Genetics Studies and Conservation Implicationssupporting
confidence: 62%
See 1 more Smart Citation
“…This study highlights the importance of using genetic data in the risk analysis of a species, as suggested by Garner et al [8], Victorino et al [16], and Lanes et al [17]. The genetic results and simulations included in the MER [26] suggest that the species is in danger of extinction and not threatened, as reported by Clark-Tapia et al [21] using only ecological data.…”
Section: Genetics Studies and Conservation Implicationssupporting
confidence: 62%
“…Although genetic studies are important toward the species conservation, these results are rarely included in the Red List of threatened species of the International Union for Conservation of Nature's (IUCN) methodology [8,[15][16][17]. Several authors have suggested the importance of incorporating genetic information in the red list criteria, since currently considered parameters are insufficient criteria of the ecological and evolutionary resilience of the species to global change, including land-use and climatic changes [16,17]. Presently, the Red List is focused on recent, current, or future threats related to sustainable habitat loss, population size, or exploitation levels [18].…”
Section: Introductionmentioning
confidence: 99%
“…At the 2016 World Conservation Congress, IUCN resolution 104 asked its member states to recognize, protect, and manage forest genetic units, whereas the 2020 IUCN resolution 109 calls for increased integration of genetic diversity into all IUCN planning activities, including protected area planning and natural capital. On the other hand, although the IUCN Red List, the globally most important species’ assessment tool, recognizes that the degree of genetic exchange is an important criterion for delimiting populations, it does not systematically incorporate genetic concepts or data into its threat assessment methodology, although proposals have been made for this (Willoughby et al 2015 , Vitorino et al 2019 , Garner et al 2020 ).…”
Section: Second Set Of Conditions: Monitoring Toolsmentioning
confidence: 99%
“…Life-history traits such as diet and body mass strongly influence the genomic diversity of species [5,23,24]. For instance, smaller bodied bird species are more threatened by habitat loss and modification [25], whereas larger bodied species are more at risk of extinction from direct effects from humans [26].…”
Section: Introductionmentioning
confidence: 99%